Enhancing Historical Learning Outcomes: A Virtual Tour with Google Earth and YouTube in Indonesian Vocational Schools - Tazkia Kamila Sofuan; Andy suryadi; Andriyanto Andriyanto (Indonesian Journal of History Education, 2025)
This quasi-experimental study investigates the impact of a digital virtual tour, integrating Google Earth and YouTube, on the history learning outcomes of vocational high school (SMK) students in Indonesia. Addressing the common challenges of low student interest and abstract historical concepts, the intervention provided an immersive, context-rich learning experience. The research involved an experimental group (n=32) using the virtual tour and a control group (n=32) with conventional instruction. Results from pretest-posttest analyses show a significantly higher improvement in the experimental group, with an N-Gain score of 0.69 (moderate effectiveness) compared to 0.22 (low effectiveness) in the control group. Simple linear regression analysis confirmed a positive and significant influence (sig. <0.001), with the model explaining 81.2% of the variance in learning outcomes. The findings demonstrate that this integrated digital media approach is an effective and innovative pedagogical tool for making history more tangible and improving student achievement in vocational education contexts.